2018
DOI: 10.1373/clinchem.2017.281295
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Detection and Quantification of AR-V7, AR-FL, PSA, and KRAS Point Mutations in Circulating Tumor Cells

Abstract: BACKGROUND Liquid biopsies can be used in castration-resistant prostate cancer (CRPC) to detect androgen receptor splice variant 7 (AR-V7), a splicing product of the androgen receptor. Patients with AR-V7-positive circulating tumor cells (CTCs) have greater benefit of taxane chemotherapy compared with novel hormonal therapies, indicating a treatment-selection biomarker. Likewise, in those with pancreatic cancer (PaCa), KRAS mutations act as prognostic biomarkers. Thus, there is an urgent need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 41 publications
1
64
1
Order By: Relevance
“…These workflows were combined with Parsortix system enabling the recovery of higher quality RNA 31 . El-Heliebi et al compared three different CTC isolation systems for gene expression and DNA mutation analysis in CTCs of prostate cancer patients and showed also differences 32 . The incorporation of microfluidics into CTC isolation is now emerging for clinical applications 33 .…”
Section: Discussionmentioning
confidence: 99%
“…These workflows were combined with Parsortix system enabling the recovery of higher quality RNA 31 . El-Heliebi et al compared three different CTC isolation systems for gene expression and DNA mutation analysis in CTCs of prostate cancer patients and showed also differences 32 . The incorporation of microfluidics into CTC isolation is now emerging for clinical applications 33 .…”
Section: Discussionmentioning
confidence: 99%
“…applied KRAS as a marker for CTC enumeration and molecular characterization. They used an in vivo isolation of CTCs (GILUPI CellCollector ® ) directly from the vein of patients and applied signal amplification of in situ padlock probes via rolling‐circle amplification: 47% (7/15) of patients were CTC‐positive (range, 1–3 CTCs/patient), and 40% (6/15) of patients had KRAS mutant CTCs (El‐Heliebi et al ., ).…”
Section: Clinical Application Of Ctcs In Pdacmentioning
confidence: 97%
“…Interestingly, El-Heliebi et al applied KRAS as a marker for CTC enumeration and molecular characterization. They used an in vivo isolation of CTCs (GILUPI CellCollector Ò ) directly from the vein of patients and applied signal amplification of in situ padlock probes via rolling-circle amplification: 47% (7/15) of patients were CTC-positive (range, 1-3 CTCs/patient), and 40% (6/15) of patients had KRAS mutant CTCs (El-Heliebi et al, 2018). With regard to the enrichment strategies, size-based filtering strategies exhibited higher sensitivity in isolating CTCs compared with EpCAM-based approaches in patients with metastatic or inoperable pancreatic cancer: ISET and CellSearch Ò detected CTCs in 88.9% (38/50) and in 39.6% (21/53) of patients, respectively (Khoja et al, 2012).…”
Section: Detectionmentioning
confidence: 99%
“…25 Padlock probe technology that is easily applicable in routine laboratories and compatible with multiple CTC-isolation devices enables quantification of AR-V7, AR-FL, PSA, and KRAS mut/wt transcripts in CTCs. 72 Recently, it was also shown that a biomarker panel containing CTC number and lactate dehydrogenase (LDH) levels was a surrogate for survival at the individual patient level in a clinical trial of abiraterone acetate plus prednisone vs prednisone alone for patients with metastatic CRPC. 73 Analysis of CTC gene expression revealed a clinically prognostic "liquid biopsy" signature in patients with metastatic castrate-resistance PCa.…”
Section: Prostate Cancermentioning
confidence: 99%